Effect of Oral Administration of Paraquat Pesticide on the Hippocampus and Substantia Nigra in Wistar Rats' Brains - Zaalan, Ebtihajah Abd Alrazaq; Qassem, Mahmoud; Bilal, Muhammad Muayyad; Tahan, Zaher Samman (Journal of agricultural, environmental and veterinary sciences, 2021)
This study aimed to detect the neurohistological damages of chronic exposure to low levels of pesticide (paraquat) in the hippocampus, and substantia nigra in Wistar rats' brains. The neurotoxic effects of acute poisoning are well established but the possibility that low level exposure causes different diseases is controversialIt is important to get a clear answer to this question as more individuals are at risk of low level exposure than acute poisoning. The anatomical and histological of current study to affected brains showed cells display the cytological changes of herbisecticides-lesioned brain tissue, such as a significant decrease in the size of the brain was observed, as most of its external features disappeared. in addition, we detected vacuolization around cells that degenerated because many reasons like apoptosis or necrosis, and the intracellular neurofibrillary tangles were observed at many regions such as the hippocampus and substantia nigra. Moreover extracellular amyloid plaques take fibers form were detected. we also observed degenerated in CA1, CA2 and CA3 regions (molecular layer, polymorphic layer and pyramidal layer) by pigmenting degenerated neurons with silver nitrate with increased astrocytes of glia cells.
Keywords: Paraquat; Hippocampus; Substantia Nigra; Neurotoxic; Cell Degeneration; Male Wistar Rat